Plasmon-assisted grafting of anisotropic nanoparticles - spatially selective surface modification and the creation of amphiphilic SERS nanoprobes - Olshtrem, Anastasiya; Guselnikova, Olga; Postnikov, Pavel; Trelin, Andrey; Yusubov, Mekhman; Kalachyova, Yevgeniya; Lapcak, Ladislav; Cieslar, Miroslav; Ulbrich, Pavel; Svorcik, Vaclav; Lyutakov, Oleksiy (Nanoscale, 2020)
Amphiphilic nanoparticles (NPs) with a spatially selective distribution of grafted functional groups have great potential in the field of sensing, advanced imaging, and therapy due to their unique surface properties. The main techniques for the spatially selective functionalization of NPs utilize the surface-assisted approaches, which significantly restrict their production throughput. In this work, we propose an alternative plasmon-based route for the spatially selective grafting of anisotropic gold nanorods (AuNRs) using iodonium and diazonium salts. Utilization of longer laser wavelengths leads to the excitation of longitudinal plasmon resonances on AuNR tips, plasmon-assisted homolysis of the C-I bond in iodonium salts and the formation of aryl radicals, which are further grafted to the tips of AuNRs. The sides of AuNRs were subsequently decorated through spontaneous diazonium surface grafting. As a result, the AuNRs with spatially separated functional groups were prepared in a versatile way, primarily in solution and without the need for a sophisticated technique of NP immobilization or surface screening. The versatility of the proposed approach was proved on three kinds of AuNRs with different architectures and wavelength positions of plasmon absorption bands. Moreover, the applicability of the prepared amphiphilic AuNRs was shown by efficient trapping and SERS sensing of amphiphilic biomolecules.